-a(-a)3=180

Simple and best practice solution for -a(-a)3=180 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -a(-a)3=180 equation:


Simplifying
-1a(-1a) * 3 = 180

Remove parenthesis around (-1a)
-1a * -1a * 3 = 180

Reorder the terms for easier multiplication:
-1 * -1 * 3a * a = 180

Multiply -1 * -1
1 * 3a * a = 180

Multiply 1 * 3
3a * a = 180

Multiply a * a
3a2 = 180

Solving
3a2 = 180

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Divide each side by '3'.
a2 = 60

Simplifying
a2 = 60

Take the square root of each side:
a = {-7.745966692, 7.745966692}

See similar equations:

| -8n+4(1+5n)=-6n-14n | | -13-12x=11-10x | | -x+9=2x+30 | | 7h-6=8-7h | | -2x+15=45-8x | | 22x+4=14x+28 | | -2x-3=x-15 | | -80.1+n=-86 | | 12x-3+105=180 | | 5+x/4=12 | | 10(x+2)=-80 | | 18-3x=3x | | ab-3a+2b-6= | | -4(x+2)-41=3-16 | | 10(x-9)=-80 | | 8x-7=4x+3 | | 8(x)(x)+40x= | | 8+6/-4-3=-10 | | 21x+8-24x=1-8 | | 21x+8-24x=1-7 | | -20=k+15-8k | | -20=k | | 25x+6-27x=5-7 | | 25x+6-27=5-7 | | -4(1-16a)=124 | | X^6+3=11 | | -5(1+4k)=-85 | | 25x+7-27x=2-5 | | 3log[2]x=8 | | 22x+6-24x=4-6 | | X*6+3=11 | | -11(a-13)=11 |

Equations solver categories